a) (x²-1)(x-2)(x+3)≤ 0
(x-1)(x+1)(x-2)(x+3)≤0
-3-112
+ - + - +
x∈[-3; -1]∪[1; 2]
б) (x²-25)(x-2)(x-4)≥0
(x-5)(x+5)(x-2)(x-4)≥0
-5245
+ - + - +
x∈(-∞; -5] ∪[2; 4]∪[5; +∞)
в) (x²-2x-8)(x+5)≤ 0
(x²-4x+2x-8)(x+5)≤ 0
(x(x-4)+2(x-4))(x+5)≤ 0
(x+2)(x-4)(x+5)≤0
-5-24
- + - +
x∈(-∞; -5] ∪[2; 4]
г) (x²+2x-15)(x-1)≥ 0
(x²-3x+5x-15)(x-1)≥ 0
(x(x-3)+5(x-3))(x-1)≥ 0
(x-3)(x+5)(x-1)≥0
-513
- + - +
x∈[-5; 1]∪[3; +∞)
д) (x² -16)(x²+2x-8)(x-2)≤ 0
(x-4)(x+4)(x-2)(x+4)≤0
(x-4)(x+4)²(x-2)≤0
-424
+ + - +
x∈[2; 4]
е) (x²-9)(x²+x-6)(x+5)≥ 0
(x-3)(x+3)(x-1)(x+5)(x+5)≥0
(x-3)(x+3)(x-1)(x+5)²≥0
-5-313
- - + - +
x∈[-3; 1]∪[3; +∞)
x ∈ (-∞; -5)∪(-3;2)
Объяснение:
2-x>0
x<2
x ∈ (-∞; -5)∪(-3;2)